Partnering to Harmonize IRBs for Community-Engaged Research to Reduce Health Disparities - Hammatt, Zoë H. (2011)
Emerging advances in health disparities research include controlled trials and comparative effectiveness studies that are frequently conducted at multiple community and academic sites. Review by different institutional review boards (IRBs) presents a major impediment to the timely and effective conduct of such research. When research involves minority and underserved communities as well as multiple geographic regions, institutional requirements and interpretation of ethical standards may vary substantially. Such variations can complicate the informed consent process and research protocol, and may undermine participant respect and trial quality. In addition, multiple IRB review can lead to unnecessary delays, jeopardizing funding and capacity to perform collaborative projects. In response to these issues, the Research Centers in Minority Institutions (RCMI) Translational Research Network (RTRN) is developing a community-partnered approach to streamlining IRB review across its consortium of 18 RCMI grantee institutions that will ensure compliance while enhancing the quality of health disparities research.